Karakterisasi Beberapa Sifat Kualitatif dan Kuantitatif Plasma Nutfah Ubi Kayu (Manihot esculenta Crantz.) - Nani Zuraida (Buletin Plasma Nutfah, 2010)
Utilization of cassava plant genetics resourcescould be done when the agronomical and morphologicalcharacters are available. Qualitative and quantitative of plantcharacters have been studied during April-December 2006 atCikeumeuh Experimental Station, Bogor. A total of 225accessions cassava germplasm were planted in 2 m x 3 m plotsize with 100 cm x 60 cm plant spacing. The plants werefertilized by 60 kg N, 20 kg P2O5, and 90 kg K2O per ha. Onethird N and K fertilizers, and all of P were applied at plantingtime, while two third N and K were applied at 3 months afterplanting. The result showed that coefficient variation ofqualitative and quantitative characters data of cassavaaccessions collected showed high variation. Therefore theaccessions are going to be maintained and conserved forgenetic resources. The plant height, number of tuber, greenmatter weight, and harvest index were positive correlation withtuber weight. While stem diameter and character of leaf lobedid not correlate with tuber weight. Among qualitativecharacters (the colors of young leaf, leaf vein, leaf stalk length,leaf lobe, stem, tuber, and number of leaf lobe) did not showdifference on tuber weight.